Clarification of the Nutritional Composition and Related Evidence for Nutritious Food Supplements in Pregnancy for Undernourished Women. (29th May 2020) - Jakazi, Chioniso; Perumal, Nandita; Sudfeld, Christopher; Smith, Emily
Abstract: Objectives: As the evidence showing the benefits of nutritious food supplements in pregnancy has grown, new products and related research has emerged. Along with these advances has also come some confusion around product-related terminology and difficulty in synthesizing and comparing the evidence base. The objective of this study is to define specific categories of nutritious supplemental food for pregnancy, review the nutritional composition and evidence for these products, and summarize the evidence. Methods: We identified relevant studies by doing an umbrella review. For each study, we abstracted data about the nutritional composition of the food supplement, as well as the trial results. To identify ongoing studies, we searched ClinicalTrials.gov and the International Clinical Trials Registry Platform for "Balanced Energy Protein, " or "Lipid Nutrients." Results: Over the last 4 decades, 17 trials including 9030 women have assessed the safety and efficacy of balanced energy and protein (BEP) supplementation during pregnancy. There is considerable heterogeneity in the nutritional composition of products used in the trials. The daily food supplement tested in trials ranged in calories from 59 kcal to 1500 kcals. The macronutrient composition averaged 66 kcals of protein and 16 kcals of fat. There was variation in the vitamin and mineral content of the supplements. We identified three new studies that will test BEP supplements with standardized macronutrient and micronutrient composition. Conclusions: Despite heterogeneity in the nutritional composition of BEP supplements in previous trials, there is clear evidence that nutritious food supplements for undernourished women can improve birth outcomes. New trials, based on standard product formulations with the potential for scale-up will provide additional evidence and a path forward for implementation. Funding Sources: There was no funding for this study.